Analisis penerapan standar akuntansi pemerintah dalam penyusunan laporan keuangan - Benediktus Mbake L Ndate; Henrikus Herdi; Thadeus Fransesco Quelmo Patty; Magdalena Nona Ice (Journal of Accounting and Digital Finance, 2025)
This study aims to discuss the preparation and implementation of accounting standards, as well as the characteristics of financial reports, at the Population Control and Family Planning, Women's Empowerment, and Child Protection Office of Sikka Regency. Data were obtained through interviews with the Head of the Office, the Treasurer, the Central and Regional Financial Analysts, and the Planners. The results indicate that the accounting process has been carried out systematically, from transaction recording to reporting, involving coordination among various units within the Regional Government Organisation. However, several obstacles, such as technical issues with the Regional Government Information System application and a lack of training for human resources in managing accrual-based Government Accounting Systems, affect the quality of financial reports. Nevertheless, with training and system updates, government accounting standards provide significant benefits, such as supporting the integration of financial processes, reducing repetitive work, expediting fund disbursement, and improving the quality of reports. This system also enables real-time monitoring, accelerates audits, and supports data-driven decision-making. However, design improvements and enhanced user capacity are still needed.